Numerical Heat Transfer and Fluid Flow 2023 (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The articles gathered in the Special Issue ‘Numerical Heat Transfer and Fluid Flow 2023’ regard applied fluid mechanics and heat transfer, including Newtonian, non-Newtonian, single or two-phase flows. Gathered research presents experiments and numerical predictions of convective heat transfer in varying engineering applications, including gas turbines, pipe transportation, geothermal, and photovoltaic modules. Experiments refer to the visualisation of air flow during natural convection, while numerical predictions are based mainly on the RANS and LES approach. New approaches in the modelling of turbulence in near-wall region and methods of intensification of heat exchange using active or passive methods can be found as well. The reprint will allow one to contribute to a better understanding of some phenomena and the interpretation of computed and measured quantities.